2022
DOI: 10.33367/psi.v7i2.2859
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Students' Psychological Well-Being in Istanbul, Turkey

Abstract: This qualitative study aims to determine and analyze Indonesian students' psychological well-being in Turkey. In addition, it is intended to explore students' experiences when studying in Turkey and reveal what and how vigorous efforts were made to adapt to a new country. The research approach used was phenomenology, which pays more attention to the individual's subjective experience. The researchers then interviewed students who had just lived in Turkey for one year and students who had been in Turkey for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Türkiye has various unique cultures and is inherent in the cultural identity of its people (Paksoy & Çelik, 2019;Rahmatullah et al, 2022). Apart from that, Turkish culture also has a long history and is often associated with the history of Islamic progress (Muvid, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Türkiye has various unique cultures and is inherent in the cultural identity of its people (Paksoy & Çelik, 2019;Rahmatullah et al, 2022). Apart from that, Turkish culture also has a long history and is often associated with the history of Islamic progress (Muvid, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In his study, Yilmaz (2018) found that the Turkish language used in daily conversation differs from the academic language used in lectures. In addition, some students also experience difficulties in learning Turkish due to differences in cultural backgrounds which also affect the structure and logic of the Turkish language (Kesten et al, 2010;Özoğlu et al, 2015;Rahmatullah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation